Obtaining Silicon Oxide Nanoparticles Doped with Fluorine and Gold Particles by the Pulsed Plasma-Chemical Method; Journal of Nanotechnology; Vol. 2019 - Kholodnaya G. E. Galina Evgenievna; Sazonov R. V. Roman Vladimirovich; Ponomarev D. V. Denis Vladimirovich; Zhirkov I. S. Igor Sergeevich (2019, 2019)
Title screen